International Delphi Consensus Study on disposable single-use endoscopy: A path to clinical adoption - Repici, Alessandro; Khalaf, Kareem; Troncone, Edoardo; Subramaniam, Sharmila; Hassan, Cesare; Bhandari, Pradeep (Digestive and liver disease, 2024)
BACKGROUND/OBJECTIVE: Increasing infectious rate estimates and low microbiological surveillance affect safety of gastrointestinal endoscopy globally. Single use endoscopes and accessories have been claimed to improve safety, but there is lack of data on their indication and sustainability. We aimed to identify a series of best practice recommendations for the use of single use endoscopes and accessories using a modified Delphi. METHODS/DESIGN: Consensus statements for the use of single use endoscopy and accessories were developed using a modified Delphi process, utilizing an international endoscopist expert panel of 62 experts from 33 nations. The main steps in the process were selecting the consensus group, conducting systematic literature reviews, developing statements, and anonymous voting on the statements until consensus was reached. High-risk patients were defined as those with multi-drug-resistant infections, immunosuppressive medication or chemotherapy, post-transplantation, or with severe neutropenia. RESULTS: Of the 26 statements that were voted upon through two rounds, 17 statements reached consensus. Category 1: single use accessories (8 statements), related to defining recommendations for the use of single use accessories in all patient populations or high-risk patients. Category 2: clinical indication for single use endoscopes (9 statements), including indications to high-risk patients, protecting the endoscope apparatus and contamination measures in endoscopy units. Category 3: technical factors (4 statements), related to superior performance and technical specifications with the new innovation. Category 4: environmental issues (2 statements), concerning mechanisms that reduce the detrimental burden to the environment. Category 5: financial implications (3 statements), related to healthcare policies, cost neutrality and other financial associations of single use endoscopy. CONCLUSIONS: This is the first international initiative in determining clinical indications for single use endoscopy and accessories. The study's findings should serve as a framework for future physicians to guide future research and aid the proper evidence-based indications for the implementation of single use endoscopes in clinical practice.
Keywords: lidé; delfská metoda; Humans; gastrointestinální endoskopie; konsensus; Delphi Technique; Consensus; Endoscopy, Gastrointestinal